OPINI PEMILIK DAN PENJAGA WARUNG SERTA MASYARAKAT TERHADAP PERINGATAN KESEHATAN BERGAMBAR PADA BUNGKUS ROKOK DI KABUPATEN BANYUWANGI: Banyuwangi Shop Owners, Shopkeepers and Community Members’ of Pictorial Health Warning on Cigarette Packs - Gayatri Ayodhya; Susy Sebayang; Desak Made Sintha Kurnia Dewi; Syifa'ul Lailiyah (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2019)
ABSTRACT Pictorial health warnings must be included in the packaging of tobacco products. It has been regulated by Health Minister of Republic Indonesia number 28 of 2013 about Inclusion of Pictorial Health Warnings and Health Information on Tobacco Product Packaging since June 24, 2014. The purpose of this study was to look an overview opinions regarding pictorial health warnings to Banyuwangi shop owners, shopkeepers and community. A cross-sectional study was conducted using secondary data from the policy evaluation survey, ban on outdoor cigarette advertising in Banyuwangi. The respondent was interviewed about the opinion consisted of 114 shop owners and shopkeepers who displayed cigarette advertisements and 131 community randomly selected. The results showed 86.9% of shop owners, 85.7% of shopkeepers and 87.8% of community agreed or strongly agreed with the pictorial health warnings and if the picture was enlarged, as many as 67.7% of shop owners, 61.9% of shopkeepers and 72.5% of community agreed or strongly agreed. 56.9% of shop owners and 28.6% of shopkeepers, and 40.5% community stated the pictorial health warnings didn’t make them not smoke. In addition, as many as 45.2% of shop owners and 42.9% of shopkeepers and 52.7% of community agreed or strongly agreed that cigarette packs were not displayed in stalls. 87,3% respondent agree that pictures of health warnings on cigarette packs but only 69,8% agree if the picture is enlarged. The picture is not enough to prevent people from smoking. Nearly half of the respondent agreed to ban the display of cigarette packs in stalls.